Extended Gravity - Morales, Eduardo; Sheu, Gloria; Zahler, Andrés (Review of Economic Studies, 2019)
Abstract Exporting firms often enter foreign markets that are similar to their previous export destinations. We develop a dynamic model in which a firm’s exports in a market may depend on how similar the market is to the firm’s home country (gravity) and to its previous export destinations (extended gravity). Given the large number of export paths from which forward-looking firms may choose, we use a moment inequality approach to estimate our model. Our estimates indicate that sharing similarities with a prior export destination in terms of geographic location, language, and income per capita jointly reduces the cost of foreign market entry by 69–90%. Reductions due to geographic location (25–38%) and language (29–36%) have the largest effect. Extended gravity thus has a large impact on export entry costs.